Fractal Dimension for the Nonautonomous Stochastic Fifth-Order Swift–Hohenberg Equation - Yanfeng Guo; Chunxiao Guo; Yongping Xi (Complexity)
Some dynamics behaviors for the nonautonomous stochastic fifth-order Swift–Hohenberg equation with additive white noise are considered. The existence of pullback random attractors for the nonautonomous stochastic fifth-order Swift–Hohenberg equation with some properties is mainly investigated on the bounded domain and unbounded domain, through the Ornstein–Uhlenbeck transformation and tail-term estimates. Furthermore, on the basis of some conditions, the finiteness of fractal dimension of random attractor is proved.